European congress of physical education (Fiep Bulletin - online, 2015)
As this bulletin announced the study center for physical education, in Bologne, organized from the 7th to 9th April 1967, a European Congress of Physical Education under the high patronage of the ministry of Public Instruction and the auspices of the University of Bologne. The president of the FIEP was honoured with an invitation in very favourable conditions.